Pyrolysis gasoline hydrogenation catalyst, its preparation method and application
By using mixed alumina and silicon oxide as support and nickel as active components, the catalyst is prepared by kneading and molding, which solves the problems of long production cycle, high cost and low catalyst activity in the traditional method, and achieves efficient and stable preparation of cracked gasoline hydrogenation catalysts.
Patent Information
- Application Number
- CN202111224480.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-20
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2041-10-20
AI Technical Summary
In the prior art, the impregnation method has a long production cycle and high cost, and the catalyst active components prepared by the traditional kneading method are difficult to reduce, have low activity, and are prone to coking inactivation.
Using mixed phase alumina (α-phase alumina and θ-phase alumina) and silicon oxide as support, the active component nickel is kneaded and kneaded with the support through a solution containing nickel and acid. The catalyst is prepared after drying, calcining and reduction, and the pore distribution of the catalyst is controlled to improve activity.
The efficient preparation of the catalyst is achieved, and it has excellent hydrogenation activity of conjugated dienes, which can reduce the value of cracked gasoline dienes while maintaining the bromine price not significantly reduced, improving the stability and impurity resistance of the catalyst.
Smart Images

Figure CN115990483B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic hydrogenation, and specifically relates to a pyrolysis gasoline hydrogenation catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] Pyrolysis gasoline is a by-product during the production of ethylene and propylene by hydrocarbon pyrolysis, with a production volume of 60 - 80 wt% of the ethylene production capacity, and it is an important raw material for extracting aromatic hydrocarbons. Since pyrolysis gasoline contains a large amount of unsaturated hydrocarbons, it has poor stability and needs to be subjected to two-stage hydrogenation treatment before further processing and utilization. The main purpose of the first-stage hydrogenation of pyrolysis gasoline is to selectively hydrogenate conjugated dienes and alkenyl aromatic hydrocarbons therein into monoolefins and alkyl aromatic hydrocarbons. Industrially, noble metal palladium-based catalysts or non-noble metal nickel-based catalysts are generally selected for the first-stage selective hydrogenation.
[0003] In recent years, affected by the increase in pyrolysis depth and the impurity content in pyrolysis raw materials, the impurity content such as sulfur, arsenic, and water in pyrolysis gasoline has increased significantly. The anti-impurity ability of traditional palladium-based catalysts is significantly insufficient, resulting in a shortened operation cycle. Due to reasons such as a high content of active components and differences in catalyst structures, nickel-based catalysts have significantly better anti-impurity ability than palladium-based catalysts, and at the same time, nickel-based catalysts also have obvious price advantages.
[0004] Patent CN109355095B improves the activity and impurity resistance of nickel-alumina catalysts by adding nickel-doped lanthanum ferrite to the carrier; Patent CN103084171A discloses a preparation method of a Pd-based pyrolysis gasoline first-stage hydrogenation catalyst. The metal active components of the catalyst are prepared by a microemulsion method and then loaded onto the carrier after reduction, finally obtaining Pd particles with uniform dispersion and small size. This catalyst is applied to the selective hydrogenation reaction of dienes and styrene, and has high activity, selectivity, and colloid tolerance; Patent CN101429453B uses an alumina carrier mainly of the θ-type and a mixed crystal form of θ and α, and through the modification of promoters such as lanthanum, cerium, and alkaline earth metal elements, the obtained Pd-based catalyst can still be used after regeneration after coking deactivation, and has good tolerance to trace water and gum; Patent CN103657670A discloses a nickel-alumina catalyst with mesoporous / macroporous or double mesoporous composite channels. The catalyst uses nickel as the main active component and at least one of molybdenum, potassium, magnesium, and lanthanum as a promoter. The obtained catalyst is applied to pyrolysis gasoline hydrogenation, has high selectivity for diene hydrogenation, good stability, strong arsenic tolerance and anti-gum ability, and the average diene hydrogenation rate is 99%.
[0005] The core of the pyrolysis gasoline hydrogenation technology is the hydrogenation catalyst. Currently, nickel catalysts are conventionally prepared by the impregnation method. This method requires preparing an impregnation solution first, forming a carrier, and then performing the impregnation, drying, and calcination processes 1 - 3 times on the carrier, followed by reduction to obtain the catalyst. Compared with the conventional impregnation method, the kneading method omits the impregnation process and directly adds the active component during the carrier forming process. After forming, through one drying, calcination, and reduction, the catalyst can be obtained. This preparation method has a simple process, no waste liquid or waste water, reduces costs and production cycles, and is an economical, green, and environmentally friendly preparation method.
[0006] However, in the current kneading method, since nickel salts are prone to strong interaction with the catalyst, nickel aluminate spinel that is difficult to reduce is formed, affecting the activity of the catalyst. Moreover, to ensure the strength of the catalyst, strong peptization of alumina is required, resulting in the generation of a large number of micropores, making the catalyst prone to coking and deactivation. Summary of the Invention
[0007] Aiming at the problems of the long production cycle and high cost of the impregnation method in the prior art, and the difficult reduction and low activity of the active components of the catalyst prepared by the traditional kneading method, the present invention provides a new pyrolysis gasoline hydrogenation catalyst, its preparation method, and application. The preparation process of the method of the present invention is simple, and the prepared catalyst has excellent conjugated diene hydrogenation activity, can significantly reduce the diene value of pyrolysis gasoline while keeping the bromine value not significantly reduced.
[0008] The first aspect of the present invention provides a pyrolysis gasoline hydrogenation catalyst, which includes a carrier and an active component nickel. The carrier includes alumina and silica, wherein the alumina contains α - phase alumina and θ - phase alumina. Based on the mass of the alumina, the content of θ - phase alumina is 75% - 95%; in the catalyst, the pore volume of pores with a pore diameter of 5 nm - 15 nm accounts for more than 50% of the total pore volume, preferably 55% - 95%.
[0009] Further, in the carrier, based on the mass of the alumina, the content of θ - phase alumina is 75% - 95%, and the content of α - phase alumina is 5% - 25%.
[0010] Further, based on the mass of the carrier, the content of the alumina is 60% - 98%, preferably 70% - 90%, and the content of silica is 2% - 40%, preferably 10% - 30%.
[0011] Further, based on the mass of the catalyst, the content of the active component nickel is 8% - 25%, preferably 10% - 20%.
[0012] Further, the total pore volume of the pyrolysis gasoline hydrogenation catalyst is 0.4 cm 3 / g or more, preferably 0.5 - 0.8 cm 3 / g; the specific surface area is 200 m2 above / g, preferably 220 - 350 m 2 / g.
[0013] In the second aspect of the present invention, a method for preparing the above-mentioned pyrolysis gasoline hydrogenation catalyst is provided, including:
[0014] (1) Prepare a solution containing nickel and an acid;
[0015] (2) Mix θ-phase alumina, α-phase alumina and silica;
[0016] (3) Knead and form the solution obtained in step (1) with the mixture obtained in step (2) to obtain a formed product;
[0017] (4) The formed product obtained in step (3) is dried, calcined and reduced to obtain a pyrolysis gasoline hydrogenation catalyst.
[0018] Further, the nickel source used in step (1) is one or more of nickel nitrate, nickel acetate and nickel sulfate.
[0019] Further, the acid used in step (1) is one or more of nitric acid, sulfuric acid, acetic acid, phosphoric acid and citric acid.
[0020] Further, the mass of the acid in step (1) is 0.1% - 5.0% of the total mass of θ-phase alumina, α-phase alumina and silica used in step (2).
[0021] Further, in step (2), alumina (i.e., θ-phase alumina and α-phase alumina) accounts for 60% - 98% of the total mass of alumina and silica, preferably 70% - 90%.
[0022] Further, the alumina in step (2) is a mixed-type alumina composed of α-phase alumina and θ-phase alumina, where θ-phase alumina accounts for 75% - 95% of the total mass of alumina, and the rest is α-phase alumina.
[0023] Further, the mass of the solution containing nickel and acid in step (3) is 50% - 120% of the mass of the mixture in step (2).
[0024] Further, during the kneading process in step (3), 2% - 10% of the mass of the mixture in step (2) of talc powder and 2% - 10% of gelatin need to be added.
[0025] Further, the drying conditions in step (4) are drying at 80 - 140 °C for 2 - 10 hours; the calcination conditions are calcining at 350 - 550 °C for 2 - 6 hours; the reduction conditions are reducing in a hydrogen atmosphere at 350 - 550 °C for 5 - 30 hours.
[0026] The third aspect of the present invention provides the application of the above-mentioned pyrolysis gasoline hydrogenation catalyst in the reaction of pyrolysis gasoline hydrogenation to remove conjugated dienes.
[0027] Further, the application includes: in a hydrogen atmosphere, contacting pyrolysis gasoline with the catalyst described in the first aspect for reaction, and the reaction conditions are as follows: the reaction temperature is 35 - 100 °C, preferably 45 - 80 °C, the reaction pressure is 2.0 - 4.0 MPa, preferably 2.5 - 3.5 MPa, the volume space velocity of pyrolysis gasoline is 3 - 5 h -1 , and the volume space velocity of hydrogen is 90 - 450 h -1 .
[0028] Further, for the pyrolysis gasoline, its distillation range is 50 - 204 °C, the diene value is 5 - 20 gI 2 / 100 g of oil, and the bromine number is 10 - 30 gBr 2 / 100 g of oil.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] (1) The catalyst of the present invention uses mixed-phase alumina (α-phase alumina and θ-phase alumina) and silica as the carrier and the active component nickel, and controls the pore distribution of the catalyst (the pore volume of pores with a pore diameter of 5 nm - 15 nm accounts for more than 50% of the total pore volume). When used in the selective hydrogenation reaction of pyrolysis gasoline, it has a good diene hydrogenation rate.
[0031] (2) The preparation method of the catalyst of the present invention is to knead and form a solution containing nickel and acid with a mixture of θ-phase alumina, α-phase alumina and silica, especially sesbania powder and gelatin, and then obtain the catalyst of the present invention through drying, calcination and reduction. Through the preparation of each material, the catalyst has an appropriate pore distribution and catalytic performance. When this catalyst is used in the selective hydrogenation reaction of pyrolysis gasoline to remove conjugated dienes, the diene hydrogenation rate is good, and good technical effects are achieved. Description of the Drawings
[0032] Figure 1 It is the pore size distribution diagram of the catalyst obtained in Example 1. Detailed Embodiments
[0033] The present invention will be further described below through examples, but these examples do not limit the scope of the present invention in any way.
[0034] In the present invention, the pore volume, specific surface area, and pore size distribution (BET) were measured on a Tristar-3000 automatic sorptometer produced by Micromeritics in the United States. The sample was degassed under vacuum at 200 °C for 2 h, and the catalyst sample was degassed at 400 °C. Then, in liquid nitrogen, the specific surface area of the sample was measured by the nitrogen adsorption volumetric method, and the pore volume and pore size distribution were calculated according to the BJH method.
[0035] In the present invention, the diolefin hydrogenation rate (%) = (1 - diolefin in the product / diolefin in the raw material) * 100%, and the diolefin value was determined according to ASTM UOP326-2008, with the unit of gI 2 / 100 g of oil.
[0036] Example 1
[0037] (1) 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of talc powder, and 20 g of gelatin were placed in a kneader and mixed;
[0038] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) were stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid was added and mixed evenly to obtain a solution containing nickel and acid;
[0039] (3) The solution obtained in step (2) was added to the mixture obtained in step (1), kneaded, shaped, and extruded in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0040] (4) The catalyst semi-finished product described in step (3) was left to dry in air for more than 6 h, then dried at 120 °C for 4 h and calcined at 400 °C for 5 h to obtain a catalyst precursor;
[0041] (5) After the catalyst precursor described in step (4) was reduced with hydrogen at 550 °C for 20 hours, the catalyst was obtained.
[0042] Figure 1 Figure is the pore size distribution diagram of the catalyst obtained in Example 1. It can be seen from Figure 1 that in this catalyst, the pore volume of pores with a pore size of 5-15 nm accounts for 55% of the total pore volume. The total pore volume of this catalyst is 0.68 cm 3 / g, and the specific surface area is 314 m 2 / g.
[0043] This catalyst was used in the hydrogenation reaction of pyrolysis gasoline. The distillation range of the pyrolysis gasoline raw material used was 80-140 °C, the diolefin value was 10-15 gI 2 / 100 g of oil, and the bromine number was 15-25 gBr 2 / 100 g of oil, the reaction conditions were a reaction temperature of 50 °C, a pressure of 2.5 MPa, a volume hourly space velocity of 2.5 h for pyrolysis gasoline -1 , a recycle ratio of 2.0, and a volume hourly space velocity of 100 h for hydrogen -1 , and the diolefin hydrogenation rate of the product was greater than 92%, meeting the requirements for industrial application.
[0044] Example 2
[0045] (1) 200 g of θ-phase alumina powder, 60 g of α-phase alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin were placed in a kneader and mixed;
[0046] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) were stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid was added and mixed evenly to obtain a solution containing nickel and acid;
[0047] (3) The solution obtained in step (2) was added to the mixture obtained in step (1), kneaded, shaped, and extruded in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0048] (4) The catalyst semi-finished product described in step (3) was left to dry in air for more than 6 h, then dried at 120 °C for 4 h and calcined at 400 °C for 5 h to obtain a catalyst precursor;
[0049] (5) The catalyst precursor described in step (4) was reduced with hydrogen at 550 °C for 20 hours to obtain the catalyst.
[0050] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounted for 59% of the total pore volume. The total pore volume of this catalyst was 0.65 cm 3 / g, and the specific surface area was 280 m 2 / g.
[0051] This catalyst was used for the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions were the same as those in Example 1, and the diolefin hydrogenation rate of the product was 90%.
[0052] Example 3
[0053] (1) 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 10 g of carob powder, and 10 g of gelatin were placed in a kneader and mixed;
[0054] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) were stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid was added and mixed evenly to obtain a solution containing nickel and acid;
[0055] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, shape, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0056] (4) Leave the catalyst semi-finished product obtained in step (3) to stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0057] (5) Reduce the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours to obtain the catalyst.
[0058] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 55% of the total pore volume. The total pore volume of this catalyst is 0.62 cm 3 / g, and the specific surface area is 320 m 2 / g.
[0059] Use this catalyst for the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 96%.
[0060] Example 4
[0061] (1) Place 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of talc powder, and 20 g of gelatin in a kneader and mix;
[0062] (2) Dissolve 236.4 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 5 g of glacial acetic acid and mix evenly to obtain a solution containing nickel and acid;
[0063] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, shape, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0064] (4) Leave the catalyst semi-finished product obtained in step (3) to stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0065] (5) Reduce the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours to obtain the catalyst.
[0066] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 62% of the total pore volume. The total pore volume of this catalyst is 0.66 cm 3 / g, and the specific surface area is 305 m 2 / g.
[0067] Use this catalyst for the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 91%.
[0068] Example 5
[0069] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin in a kneader;
[0070] (2) Dissolve 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0071] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead, shape, and extrude in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0072] (4) Let the catalyst semi-finished product obtained in step (3) stand and dry for more than 6 h, then dry at 150 °C for 4 h and calcine at 450 °C for 5 h to obtain a catalyst precursor;
[0073] (5) After reducing the catalyst precursor obtained in step (4) with hydrogen at 530 °C for 20 hours, the catalyst is obtained.
[0074] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 63% of the total pore volume. The total pore volume of this catalyst is 0.69 cm 3 / g, and the specific surface area is 309 m 2 / g.
[0075] Use this catalyst for the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 91%.
[0076] Example 6
[0077] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin in a kneader;
[0078] (2) Dissolve 264.7 g of nickel nitrate, 1 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 2 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0079] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead, shape, and extrude in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0080] (4) Let the catalyst semi-finished product obtained in step (3) stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0081] (5) After reducing the catalyst precursor described in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0082] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 56% of the total pore volume. The total pore volume of this catalyst is 0.72 cm 3 / g, and the specific surface area is 342 m 2 / g.
[0083] This catalyst is used in the pyrolysis gasoline hydrogenation reaction. The raw materials and conditions are the same as in Example 1, and the diene hydrogenation rate of the product is 85%.
[0084] Example 7
[0085] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 30 g of carrageenan powder, and 30 g of gelatin in a kneader;
[0086] (2) Dissolve 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, and then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0087] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, form, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0088] (4) Let the catalyst semi-finished product described in step (3) stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain the catalyst precursor;
[0089] (5) After reducing the catalyst precursor described in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0090] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 73% of the total pore volume. The total pore volume of this catalyst is 0.77 cm 3 / g, and the specific surface area is 263 m 2 / g.
[0091] This catalyst is used in the pyrolysis gasoline hydrogenation reaction. The raw materials and conditions are the same as in Example 1, and the diene hydrogenation rate of the product is 87%.
[0092] Example 8
[0093] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carrageenan powder, and 20 g of gelatin in a kneader;
[0094] (2) Dissolve 152 g of nickel nitrate, 10 g of citric acid, and 30 g of water (heated to 60 °C) with stirring to form a mixed solution. Then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0095] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, shape, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0096] (4) Leave the catalyst semi-finished product obtained in step (3) to dry in air for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0097] (5) After reducing the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0098] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 63% of the total pore volume. The total pore volume of this catalyst is 0.52 cm 3 / g, and the specific surface area is 343 m 2 / g.
[0099] When this catalyst is used in the hydrogenation reaction of pyrolysis gasoline, the raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 84%.
[0100] Example 9
[0101] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin in a kneader;
[0102] (2) Dissolve 264.7 g of nickel nitrate, 10 g of citric acid, and 100 g of water (heated to 60 °C) with stirring to form a mixed solution. Then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0103] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, shape, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0104] (4) Leave the catalyst semi-finished product obtained in step (3) to dry in air for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0105] (5) After reducing the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0106] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 58% of the total pore volume. The total pore volume of this catalyst is 0.81 cm 3 / g, and the specific surface area is 254 m2 / g.
[0107] This catalyst was used in the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions were the same as those in Example 1, and the diene hydrogenation rate of the product was 86%.
[0108] Comparative Example 1
[0109] (1) 100 g of θ-phase alumina powder, 160 g of α-alumina powder, 60 g of silica powder, 20 g of carrageenan powder, and 20 g of gelatin were placed in a kneader and mixed;
[0110] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) were stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid was added and mixed evenly to obtain a solution containing nickel and acid;
[0111] (3) The solution obtained in step (2) was added to the mixture obtained in step (1), kneaded, formed, and extruded in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0112] (4) The catalyst semi-finished product described in step (3) was left to dry in air for more than 6 h, then dried at 120 °C for 4 h and calcined at 400 °C for 5 h to obtain a catalyst precursor;
[0113] (5) The catalyst precursor described in step (4) was reduced with hydrogen at 550 °C for 20 hours to obtain the catalyst.
[0114] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounted for 23% of the total pore volume. The total pore volume of this catalyst was 0.21 cm 3 / g, and the specific surface area was 89 m 2 / g.
[0115] This catalyst was used in the hydrogenation reaction of pyrolysis gasoline. The raw materials and conditions were the same as those in Example 1, and the diene hydrogenation rate of the product was 42%.
[0116] Comparative Example 2
[0117] (1) 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 20 g of carrageenan powder, and 20 g of gelatin were placed in a kneader and mixed;
[0118] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) were stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid was added and mixed evenly to obtain a solution containing nickel and acid;
[0119] (3) The solution obtained in step (2) was added to the mixture obtained in step (1), kneaded, formed, and extruded in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0120] (4) Leave the catalyst semi-finished product described in step (3) to stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain the catalyst precursor;
[0121] (5) After reducing the catalyst precursor described in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0122] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 48% of the total pore volume. The total pore volume of this catalyst is 0.54 cm 3 / g, and the specific surface area is 243 m 2 / g.
[0123] When this catalyst is used in the pyrolysis gasoline hydrogenation reaction, the raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 78%.
[0124] Comparative Example 3
[0125] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin in a kneader;
[0126] (2) Dissolve 264.7 g of nickel nitrate, 10 g of citric acid, and 150 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0127] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead, shape, and extrude in a kneader to obtain a clover-shaped catalyst semi-finished product;
[0128] (4) Leave the catalyst semi-finished product described in step (3) to stand and dry for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain the catalyst precursor;
[0129] (5) After reducing the catalyst precursor described in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0130] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 52% of the total pore volume. The total pore volume of this catalyst is 0.88 cm 3 / g, and the specific surface area is 189 m 2 / g.
[0131] When this catalyst is used in the pyrolysis gasoline hydrogenation reaction, the raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 68%.
[0132] Comparative Example 4
[0133] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, and 20 g of carob powder in a kneader;
[0134] (2) Dissolve 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 5 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0135] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, form, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0136] (4) Leave the catalyst semi-finished product obtained in step (3) to dry in air for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0137] (5) After reducing the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0138] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 49% of the total pore volume. The total pore volume of this catalyst is 0.57 cm 3 / g, and the specific surface area is 283 m 2 / g.
[0139] When this catalyst is used in the hydrogenation reaction of pyrolysis gasoline, the raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 58%.
[0140] Comparative Example 5
[0141] (1) Mix 230 g of θ-phase alumina powder, 30 g of α-alumina powder, 60 g of silica powder, 20 g of carob powder, and 20 g of gelatin in a kneader;
[0142] (2) Dissolve 264.7 g of nickel nitrate, 20 g of citric acid, and 50 g of water (heated to 60 °C) by stirring to form a mixed solution, then add 13 g of concentrated nitric acid and mix evenly to obtain a solution containing nickel and acid;
[0143] (3) Add the solution obtained in step (2) to the mixture obtained in step (1), knead in a kneader, form, and extrude to obtain a clover-shaped catalyst semi-finished product;
[0144] (4) Leave the catalyst semi-finished product obtained in step (3) to dry in air for more than 6 h, then dry at 120 °C for 4 h and calcine at 400 °C for 5 h to obtain a catalyst precursor;
[0145] (5) After reducing the catalyst precursor obtained in step (4) with hydrogen at 550 °C for 20 hours, the catalyst is obtained.
[0146] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 58% of the total pore volume. The total pore volume of this catalyst is 0.25 cm 3 / g, and the specific surface area is 92 m 2 / g.
[0147] This catalyst is used in the pyrolysis gasoline hydrogenation reaction. The raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 32%.
[0148] Comparative Example 6
[0149] (1) 320 g of θ-phase alumina powder and 20 g of carrageenan powder are placed in a kneader and mixed;
[0150] (2) 264.7 g of nickel nitrate, 10 g of citric acid, and 50 g of water (heated to 60 °C) are stirred and dissolved into a mixed solution, and then 5 g of concentrated nitric acid is added and mixed evenly to obtain a solution containing nickel and acid;
[0151] (3) The solution obtained in step (2) is added to the mixture obtained in step (1), kneaded in a kneader, formed, and extruded to obtain a semi-finished clover-shaped catalyst;
[0152] (4) The semi-finished catalyst described in step (3) is left to dry in air for more than 6 h, then dried at 120 °C for 4 h and calcined at 400 °C for 5 h to obtain a catalyst precursor;
[0153] (5) The catalyst precursor described in step (4) is reduced with hydrogen at 550 °C for 20 hours to obtain the catalyst.
[0154] In this catalyst, the pore volume of pores with a pore diameter of 5 - 15 nm accounts for 41% of the total pore volume. The total pore volume of this catalyst is 0.35 cm 3 / g, and the specific surface area is 118 m 2 / g.
[0155] This catalyst is used in the pyrolysis gasoline hydrogenation reaction. The raw materials and conditions are the same as those in Example 1, and the diene hydrogenation rate of the product is 59%.
Claims
1. A pyrolysis gasoline hydrogenation catalyst, comprising a carrier and an active component nickel, wherein the carrier comprises alumina and silica, and the alumina contains α-phase alumina and θ-phase alumina. Based on the mass of the alumina, the content of the θ-phase alumina is 75% - 95%; in the catalyst, the pore volume of pores with a pore diameter of 5 nm - 15 nm accounts for more than 50% of the total pore volume, and the total pore volume of the pyrolysis gasoline hydrogenation catalyst is 0.4 cm 3 / g or more, and the specific surface area is 200 m 2 / g or more; based on the mass of the carrier, the content of the alumina is 60% - 98%, and the content of the silica is 2% - 40%.
2. The catalyst according to claim 1, characterized in that, in the catalyst, the pore volume of pores with a pore diameter of 5 nm - 15 nm accounts for 55% - 95% of the total pore volume.
3. The catalyst according to claim 1, characterized in that, in the carrier, based on the mass of alumina, the content of θ-phase alumina is 75% - 95%, and the content of α-phase alumina is 5% - 25%.
4. The catalyst according to claim 1, characterized in that, based on the mass of the carrier, the content of the alumina is 70% - 90%, and the content of silica is 10% - 30%.
5. The catalyst according to any one of claims 1 - 4, characterized in that, based on the mass of the catalyst, the content of the active component nickel is 8% - 25%.
6. The catalyst according to any one of claims 1 - 4, characterized in that, based on the mass of the catalyst, the content of the active component nickel is 10% - 20%.
7. The catalyst according to claim 1, characterized in that, The total pore volume of the pyrolysis gasoline hydrogenation catalyst is 0.5 - 0.8 cm 3 / g; the specific surface area is 220 - 350 m 2 / g.
8. A method for preparing the pyrolysis gasoline hydrogenation catalyst according to any one of claims 1 - 7, comprising: (1) preparing a solution containing nickel and an acid; (2) mixing θ-phase alumina, α-phase alumina and silica; (3) kneading and shaping the solution obtained in step (1) with the mixture obtained in step (2) to obtain a shaped product; (4) drying, calcining and reducing the shaped product obtained in step (3) to obtain the pyrolysis gasoline hydrogenation catalyst.
9. The preparation method according to claim 8, characterized in that, the nickel source used in step (1) is one or more of nickel nitrate, nickel acetate, nickel sulfate; and / or, the acid used in step (1) is one or more of nitric acid, sulfuric acid, acetic acid, phosphoric acid, citric acid; and / or, the mass of the acid in step (1) is 0.1% - 5.0% of the total mass of θ-phase alumina, α-phase alumina and silica used in step (2).
10. The preparation method according to claim 8, characterized in that, the mass of the solution containing nickel and an acid in step (3) is 50% - 120% of the mass of the mixture in step (2).
11. The preparation method according to claim 8, characterized in that, during the kneading process in step (3), adding 2% - 10% of the mass of the mixture in step (2) of sesbania powder and 2% - 10% of gelatin.
12. The preparation method according to claim 8, characterized in that, the drying conditions in step (4) are drying at 80 - 140 °C for 2 - 10 hours; and / or, the calcining conditions are calcining at 350 - 550 °C for 2 - 6 hours; and / or, the reduction conditions are reducing in a hydrogen atmosphere at 350 - 550 °C for 5 - 30 hours.
13. Application of the pyrolysis gasoline hydrogenation catalyst according to any one of claims 1 - 7 in the reaction of hydrogenating and removing conjugated dienes from pyrolysis gasoline.
14. The application according to claim 13, characterized in that, The application includes: contacting pyrolysis gasoline with the catalyst in a hydrogen atmosphere for reaction under the following reaction conditions: the reaction temperature is 35 - 100 °C, the reaction pressure is 2.0 - 4.0 MPa, the volume hourly space velocity of pyrolysis gasoline is 3 - 5 h -1 , and the volume hourly space velocity of hydrogen is 90 - 450 h -1 .
15. The application according to claim 13, characterized in that, The application includes: contacting cracked gasoline with the catalyst in a hydrogen atmosphere for reaction under the following reaction conditions: the reaction temperature is 45 - 80 °C, the reaction pressure is 2.5 - 3.5 MPa, the volume hourly space velocity of cracked gasoline is 3 - 5 h -1 , and the volume hourly space velocity of hydrogen is 90 - 450 h -1 .
16. The application according to claim 13, 14 or 15, characterized in that, The cracked gasoline has a distillation range of 50 - 204 °C, a diolefin value of 5 - 20 gI 2 / 100 g of oil, and a bromine number of 10 - 30 gBr 2 / 100 g of oil.
Citation Information
Patent Citations
Pyrolysis gasoline cut fraction section selective hydrogenation method
CN101429453B
Pyrolysis gasoline first stage selective hydrogenation catalyst, preparation method and applications thereof
CN103084171A
Pyrolysis gasoline nickel system selective hydrogenation catalyst and preparation method thereof
CN103657670A
Selective hydrotreating method for C6-C8 distillate oils from cracked gasoline
CN109355095B
Alumina carrier, and nickel-based catalyst using alumina carrier as carrier, preparation method and applications thereof
CN106622393A